Potensi Dan Efektivitas Pemungutan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) dalam Rangka Peningkatan Pendapatan Asli Daerah (PAD) Kota Banjarmasin - Hanum Krisna Sari; Dewi Rahayu (PPJP Universitas Lambung Mangkurat, 2020)
This research aims to determine the potential and effectiveness, barriers, and strategies in the BPHTB tax collection and the projection of BPHTB tax Banjarmasin City for the upcoming five years. This research uses quantitative descriptive research methods. The data types used are primary and secondary data, with data collection techniques through interviews and documentation. The results showed that BPHTB tax Banjarmasin city is a local tax with an acceptable tax condition in raising the city of Banjarmasin. BPHTB tax effectiveness rate in Banjarmasin City during 2014-2018 has been excellent, with an average percentage of 104%. However, based on interviews, there are still some obstacles in BPHTB's tax due to invalid data, unfaithful taxpayers, lack of experts, and the local government's strategy to mitigate it by adding field officers system and updating data, and tightening supervision. The five-year projection that will be growth is always showing positive developments by 24%.